«The Left-wing Governmental Alliance in Portugal, 2015-2019: Roots, Characteristics and Results» - Freire, A. (Seminar UNED about The Left-wing Governmental Alliance in Portugal, 2015-2019, 2019)
André Freire (2019), como keynote speaker para apresentar a comunicação «The Left-wing Governmental Alliance in Portugal, 2015-2019: Roots, Characteristics and Results». The seminar took place in November 19, 2019, 12:00 – 14:00, at Universidad Nacional de Educación a Distancia (UNED) - Facultad de Ciencias Políticas y Sociología, Madrid, Spain. O keynote speaker foi apresentado pelo Professor Xavier Coller, e o discussant foi o Professor Luís Ramiro.